Decentralization and development administration in a unitary state: empowerment and development for whom? - Buendia, Rizal G
The concept of decentralization involves two features: political, whereby power and authority are devolved from the central government to the local governmental units (LGUs): and administrative, whereby functions of the national line agencies are deconcentrated to regional and field units. To date, decentralization has managed to find its place in the rhetorics of the Constitution. Its actural implementation, however, continues to face social, political and economic barriers inherent in a unitary, highly centralized, bureaucratic, and paternalistic government system. The existence of rigid national guidelines (i.e., planning and finance) and the subjection of LGUs to direct supervision from the central offic
Keywords: Development Administration; Local Government; Decentralisation - Philippines